Evaluation of pregabalin-induced oedema using the adverse event spontaneous reporting database and the prescription claims database. - Ito, Hitoshi; Hasegawa, Yoshitaka; Maeda, Mamoru; Tsukioka, Ryota; Tsuchiya, Masao; Yasuno, Nobuhiro; Oishi, Miya (International Journal of Pharmacy Practice, 2025)
Objectives Pregabalin may reduce the quality of life due to oedema, which may lead to further adverse events if co-administered with diuretics. This study investigated the occurrence of oedema and loop diuretic prescriptions in Japanese patients treated with pregabalin, including the temporal characteristics of the onset and factors associated with oedema. Methods Using the Japanese Adverse Drug Event Report database, we performed logistic regression analysis to calculate adjusted reporting odds ratios to assess the association between pregabalin and oedema, and time-of-onset analysis to identify the timing of oedema onset. Using the prescription claims database of the Japanese pharmacy group, we assessed the occurrence of loop diuretic prescriptions associated with pregabalin by calculating the adjusted sequence ratios in the prescription sequence symmetry analysis, and identified the associated factors in subgroup analyses. Key findings The adjusted reporting odds ratio was 6.89 (95% confidence interval: 5.96–7.91) for pregabalin, adjusted for age and sex as covariates. The median time to onset of oedema was 16.0 days (interquartile range: 6.0–42.0 days). The adjusted sequence ratio was 1.17 (95% confidence interval: 1.09–1.25), with subgroup analyses confirming a significant association at starting doses of 150 mg/day and more. Conclusions This study suggests that oedema and loop diuretic prescriptions are associated with pregabalin use. Pregabalin-induced oedema was more common early in treatment and loop diuretics were more likely to be prescribed when the starting dose of pregabalin was 150 mg/day or more.